How does Islamic Work Culture and Leadership, as well as Organizational Citizenship Behavior Improve Teacher Performance in Vocational High Schools (SMK)? - Nurul Qomariah; Zahrotul Janah; Dwi Cahyono (Budapest International Research and Critics University, 2023)
Vocational High School is a high school that prepares its graduates to be ready to enter the world of work. Currently the government is trying to improve the quality of graduates from this vocational school. This study has 3 (three) objectives, namely the first to determine the effect of Islamic work culture on teacher performance, the second objective to determine the effect of leadership on teacher performance and the third objective to determine the effect of OCB on teacher performance at SMK Muhammadiyah Banyuwangi. The population is all teachers who teach at SMK Muhammadiyah Banyuwangi, totaling 345 teachers. By using the Slovin formula, it is known that the number of samples is 185 teachers who are the respondents. Statistical analysis of the description is used to determine the description of the respondents and the research variables used. The data analysis used is the Structural Equation Model (SEM) using WarpPLS 7.0. The calculation results show that Islamic work culture variable (X1) has a positive and significant effect on teacher performance (Y), leadership variable (X2) has a positive and significant effect on teacher performance (Y) and organizational citizenship behavior (X3) has an effect on teacher performance at Muhammadiyah Vocational Schools Banyuwangi.